World Economic Outlook, October 2010 : Recovery, Risk, and Rebalancing. (World Economic Outlook; World Economic Outlook ;, 2010)
The recovery from the Great Recession is proceeding broadly as expected, but most advanced economies and a few emerging economies still face large adjustments, are recovering only sluggishly, and have continued high unemployment. By contrast, many emerging and developing economies are again seeing strong growth. A sustained, healthy global recovery rests on two rebalancing acts: internal rebalancing, with a strengthening of private demand in advanced economies, allowing for fiscal consolidation; and external rebalancing, with an increase in net exports in deficit countries and a decrease in net exports in surplus countries, notably emerging Asia. This edition of the World Economic Outlook examines the interactions between these two rebalancing acts and explores the policies required to support them. One of the two analytical chapters examines the effects on output and employment of fiscal consolidation in advanced economies using detailed budget data, and the other examines the collapse and recovery of trade in economies that have experienced crises.